1994
DOI: 10.1007/bf01289788
|View full text |Cite
|
Sign up to set email alerts
|

Halo signals in the beta decay of28 O

Abstract: Abstract, We present a study of the 'hypothetical', doubly magic and extremely neutron-rich nucleus 280. In our description 280 is a bound nucleus and exhibits some of the features of a neutron halo, where a particular channel for beta delayed deuteron emission is evident.PACS: 21.10. Dr; 21.10.Gv; 21.60.Cs; Nuclei at the valley of stability have very similar neutron an proton radii, even in situations (e.g. 48Ca, 2~ of large neutron excess. However, recent experimental data on light nuclei far from stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…22 ' The average binding energies in NRMF approaches also agree with Poves et a/. 's prediction' 15 ] -E/A = 6.125 MeV. For the theoretical results obtained in RMF approaches, the data are more dispersed than those in NRMF approaches.…”
supporting
confidence: 76%
“…22 ' The average binding energies in NRMF approaches also agree with Poves et a/. 's prediction' 15 ] -E/A = 6.125 MeV. For the theoretical results obtained in RMF approaches, the data are more dispersed than those in NRMF approaches.…”
supporting
confidence: 76%
“…Poves et al (139) have suggested that the as yet undiscovered and very likely unstable nudeus 280 would have a large dineutron component in the ground state, decaying to a high-lying deuteron cluster in 28F.…”
Section: Tra Nsitions Between Discrete Statesmentioning
confidence: 99%